2011
DOI: 10.2967/jnumed.111.093674
|View full text |Cite
|
Sign up to set email alerts
|

Palliation and Survival After Repeated 188Re-HEDP Therapy of Hormone-Refractory Bone Metastases of Prostate Cancer: A Retrospective Analysis

Abstract: This retrospective study compared the effects of single and multiple administrations of 186 Re-HEDP) on palliation and survival of prostate cancer patients presenting with more than 5 skeletal metastases. Methods: A total of 60 patients were divided into 3 groups. Group A (n 5 19) consisted of patients who had received a single injection; group B (n 5 19), patients who had 2 injections; and group C (n 5 22), patients who had 3 or more successive injections. The 188 Re-HEDP was prepared using non-carrieradded … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
27
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(30 citation statements)
references
References 21 publications
2
27
0
1
Order By: Relevance
“…Furthermore, patients with prostatic cancer have shown, after two [ 188 Re]Re-HEDP injections, a significantly higher response rate (92%), a prostate-specific antigen (PSA) decline >50% (38%), and a longer PFS (7 months) compared to patients who have had a single injection 52,53. Biersack et al showed an improved OS of 15.7 months in patients after repeated injections (≥3 injections) compared to patients with a single therapy 54. Besides transient bone marrow toxicity (thrombocytopenia grade III), the reported toxicity is low to moderate 51…”
Section: Introduction: Goals Of Theranostics In Nuclear Medicinementioning
confidence: 99%
“…Furthermore, patients with prostatic cancer have shown, after two [ 188 Re]Re-HEDP injections, a significantly higher response rate (92%), a prostate-specific antigen (PSA) decline >50% (38%), and a longer PFS (7 months) compared to patients who have had a single injection 52,53. Biersack et al showed an improved OS of 15.7 months in patients after repeated injections (≥3 injections) compared to patients with a single therapy 54. Besides transient bone marrow toxicity (thrombocytopenia grade III), the reported toxicity is low to moderate 51…”
Section: Introduction: Goals Of Theranostics In Nuclear Medicinementioning
confidence: 99%
“…The mean survival increased from 7 to 13 months [42] in the double-dose cohort. A more recently published retrospective analysis of these data of the same group showed, in a total number of 60 patients suffering from bone metastases of hormone-refractory prostate cancer, an improvement of the mean survival from 4.5 to 15.66 months, in the subgroup with multiple (3 and more) successive administrations of 188 Re-HEDP [43]. Similar results were published by Turner and Claringbold [44] administering, in a phase II trial, either a single or repeated activity of 153 Sm-EDTMP.…”
Section: Perspectivesmentioning
confidence: 99%
“…In another study by Palmedo et al [29] and Biersack [30], the analgesia and antitumor effects of repetitive administrations of Re-188 HEDP were evaluated in patients with metastatic prostate cancer, whereas minor toxicity problems were reported.…”
Section: Clinical Applicationsmentioning
confidence: 99%